THE HDL LEVEL IN DIABETIC FOOT ULCER PATIENTS WITH AND WITHOUT AMPUTATION AT DR. SEOTOMO GENERAL ACADEMIC HOSPITAL SURABAYA - Ahmed Eliaan Shaker Abuajwa; Hermina Novida; Heroe Soebroto; Yan Efrata Sembiring (Majalah Biomorfologi, 2023)
Highlights1. Diabetes mellitus is a category of metabolic disease characterized by uncontrolled hyperglycemia.2. This study revealed no statistically significant differences in total cholesterol, TG, LDL, HDL, or LDL/HDL ratio between amputated and non-amputated DFU patients. AbstractBackground: Diabetic foot ulcers (DFU) are microvascular and macrovascular consequences of diabetes and are associated with neuropathy, vascular disease, and immunosuppression. Increased blood glucose levels may result in the glycosylation of proteins in the nerve cells of the foot, leading to ischemia and cellular disturbances that can damage muscular, sensory, and autonomic neurons. Objective: To compare the lipid profiles of amputated and non-amputated DFU patients. Material and Method: This was a cross-sectional, analytic, retrospective research using total sample approach to analyze the medical records of all diabetes patients admitted to Dr. Soetomo General Academic Hospital between February 2018 and December 2020, with or without amputation. Result: The average age of DFU patients at Dr. Soetomo General Academic Hospital was 55.6 9.4 years, and the majority of patients were female (57%). Diabetic foot ulcers were most prevalent in the age group â‰¥50 years old (74%), amputated DFU patients had larger mean total cholesterol, TG, LDL, and HDL than non-amputated DFU patients, although the difference was not statistically significant. While the mean LDL/HDL ratio was greater in non-amputated DFU patients, the difference was statistically insignificant. The HDL level was low in 84% of amputated DFU patients, whereas in non-amputated DFU patients it was 81%. Conclusion: This research showed no significant variation in total cholesterol, TG, LDL, HDL, or the LDL/HDL ratio between amputated and non-amputated DFU patients. Most DFU patients with and without amputations had low HDL values.